2016
DOI: 10.1186/s12974-016-0661-0
|View full text |Cite
|
Sign up to set email alerts
|

The glucagon-like peptide-1 receptor agonist exendin-4 ameliorates warfarin-associated hemorrhagic transformation after cerebral ischemia

Abstract: BackgroundAs the number of patients with cardioembolic ischemic stroke is predicted to be double by 2030, increased burden of warfarin-associated hemorrhagic transformation (HT) after cerebral ischemia is an expected consequence. However, thus far, no effective treatment strategy is available for HT prevention in routine clinical practice. While the glucagon-like peptide-1 receptor (GLP-1R) agonist exendin-4 (Ex-4) is known to protect against oxidative stress and neuronal cell death caused by ischemic brain da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 58 publications
2
42
0
Order By: Relevance
“…Previously, it had been demonstrated that GLP-1R agonist exendin-4 ameliorates warfarin-associated haemorrhagic transformation after cerebral ischaemia [34]. Importantly, semaglutide has recently been shown in the SUSTAIN-6 trial to have clinical benefit in terms of reducing the rate of non-fatal stroke [34], although studies assessing functional outcome after stroke are still needed [35]. In this regard, our experimental study demonstrated improved functional recovery in rats treated with either liraglutide or semaglutide.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Previously, it had been demonstrated that GLP-1R agonist exendin-4 ameliorates warfarin-associated haemorrhagic transformation after cerebral ischaemia [34]. Importantly, semaglutide has recently been shown in the SUSTAIN-6 trial to have clinical benefit in terms of reducing the rate of non-fatal stroke [34], although studies assessing functional outcome after stroke are still needed [35]. In this regard, our experimental study demonstrated improved functional recovery in rats treated with either liraglutide or semaglutide.…”
Section: Discussionmentioning
confidence: 57%
“…Although this latter observation still needs to be confirmed by further studies, this possible characteristic of semaglutide can be valuable for the patients with acute ischaemic stroke, especially those undergoing thrombolytic therapy [31][32][33]. Previously, it had been demonstrated that GLP-1R agonist exendin-4 ameliorates warfarin-associated haemorrhagic transformation after cerebral ischaemia [34]. Importantly, semaglutide has recently been shown in the SUSTAIN-6 trial to have clinical benefit in terms of reducing the rate of non-fatal stroke [34], although studies assessing functional outcome after stroke are still needed [35].…”
Section: Discussionmentioning
confidence: 91%
“…Several studies have demonstrated a multitude of neuroprotective actions, with exendin-4-mediated PI3K surge in different areas of the CNS, leading to increase in phosphorylation of AKT via PI3K signalling pathway. This mechanism of action is thought to increase the anti- versus pro-apoptotic bcl-2 family protein balance ( Brywe et al , 2005 ; Athauda and Foltynie, 2016 ), attenuate neuroinflammation and stabilize the blood–brain barrier post-transient middle cerebral artery occlusion in non- ( Chen et al , 2016 ) and diabetic mice ( Li et al , 2016 ). Intracellular cAMP levels are also raised in exendin-4-treated post-transient middle cerebral artery occlusion as a result of increased GLP1R expression ( Teramoto et al , 2011 ; Kim et al , 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…37,50,55 GLP-1RA administration following stroke induction has been associated with an anti-inflammatory effect. 26 Tumor necrosis factor alpha (TNF-) is a cytokine synthesised by many cell linesbut particularly by macrophages and microglia. 56 TNF- is involved with the inflammatory response following stroke onset.…”
Section: Cellular Functionmentioning
confidence: 99%